Penyuluhan Bahaya Penggunaan Obat Tradisional Tanpa Resep Selama Kehamilan Terhadap Risiko Abortus - Khasanah, Uswatun; Hamzah, Abd Natsir; Vandika, Arnes Yuli (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The use of traditional medicines, passed down through generations, is still common in society, including among pregnant women. People often assume that traditional medicines are safe because they are made from natural ingredients, without considering their pharmacological effects and potential toxicity, especially during pregnancy. Some herbal remedies are known to cause uterine contractions, impaired fetal development, and even abortion. This Community Service (PKM) activity aims to increase pregnant women's knowledge about the dangers of using traditional medicines without a prescription during pregnancy. The activity was conducted at Community Health Center X, Regency Y, using an interactive counseling method for 30 pregnant women. Evaluation used pre- and post-tests to measure participants' understanding. The results showed a significant increase in participants' knowledge regarding the risks of over-the-counter use of traditional medicines. This activity demonstrates that community-based health education is an effective strategy in reducing the practice of using traditional medicines without medical supervision during pregnancy. It is hoped that this activity can become a sustainable program to reduce the number of abortions due to the use of non-standardized medicines.